2015
DOI: 10.1038/eye.2015.134
|View full text |Cite
|
Sign up to set email alerts
|

Is day-1 postoperative review necessary after pars plana vitrectomy?

Abstract: Purpose This study aimed to determine the proportion of patients requiring alteration in management based on the findings of the day-1 postoperative visit after pars plana vitrectomy, and to identify clinical characteristics that predict the need for unexpected intervention. Patients and methods A retrospective case note review was conducted of all patients who underwent pars plana vitrectomy and who then attended for review on the first postoperative day. All patients received routine prophylactic anti-glauco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…While there have been a few studies evaluating the utility of a postoperative day one visit, additional evidence is needed. 2 , 3 , 4 However, there is interest in increasing postoperative visit efficiency. This interest is highlighted by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been a few studies evaluating the utility of a postoperative day one visit, additional evidence is needed. 2 , 3 , 4 However, there is interest in increasing postoperative visit efficiency. This interest is highlighted by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…1 Complications screened for at the POD1 visit include elevated intraocular pressure (IOP), endophthalmitis, wound leaks, hypotony, choroidal detachments, corneal decompensation, and failure of retinal reattachment. 2 , 3 All of these adverse effects could have serious long-term consequences on vision if left untreated. However, anecdotal evidence and prior smaller studies suggest that the primary problem detected at the POD1 visit is an elevation in IOP, especially in eyes treated with silicone oil and gas tamponade.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Alexander et al reported that the incidence of day 1 postvitrectomy raised IOP is low with the use of postoperative prophylactic antiglaucoma treatment. 6 Therefore, a current trend is to use immediate prophylactic oral or topical antiglaucoma medication to justify avoidance of day 1 postoperative review. However, the evidence to support this approach is currently deficient and it remains questionable whether prophylactic treatment is essential in all vitreoretinal cases.…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends in visual outcomes have been reported in patients with wet AMD who were similarly switched to aflibercept. 5,6 Conflict of interest…”
mentioning
confidence: 99%